Oral Administration of Sitagliptin Activates CREB and Is Neuroprotective in Murine Model of Brain Trauma - DellaValle, Brian; Brix, Gitte S.; Brock, Birgitte; Gejl, Michael; Rungby, Jørgen; Larsen, Agnete (Frontiers in Pharmacology, 2016)
Introduction: Traumatic brain injury is a major cause of mortality and morbidity. We have previously shown that the injectable glucagon-like peptide-1 (GLP-1) analogue, liraglutide, significantly improved the outcome in mice after severe traumatic brain injury (TBI). In this study we are interested in the effects of oral treatment of a different class of GLP-1 based therapy, dipeptidyl peptidase IV (DPP-IV) inhibition on mice after TBI. DPP-IV inhibitors reduce the degradation of endogenous GLP-1 and extend circulation of this protective peptide in the bloodstream. This class has yet to be investigated as a potential therapy for TBI. Methods: Mice were administrated once-daily 50 mg/kg of sitagliptin in a Nutella® ball or Nutella® alone throughout the study, beginning two days before severe trauma was induced with a stereotactic cryo-lesion. At two days post trauma, lesion size was determined. Brains were isolated for immunoblotting for assessment of selected biomarkers for pathology and protection. Results: Sitagliptin treatment reduced lesion size at day 2 post-injury by ~28% (p<0.05). Calpain-driven necrotic tone was reduced ~2-fold in sitagliptin-treated brains (p<0.001) and activation of the protective cAMP-response element binding protein (CREB) system was significantly more pronounced (~1.5-fold, p<0.05). The CREB-regulated, mitochondrial antioxidant protein manganese superoxide dismutase (MnSOD) was increased in sitagliptin-treated mice (p>0.05). Conversely, apoptotic tone (alpha-spectrin fragmentation, Bcl-2 levels) and the neuroinflammatory markers IL-6, and Iba-1 were not affected by treatment. Conclusions: This study shows, for the first time, that DPP-IV inhibition ameliorates both anatomical and biochemical consequences of TBI and activates CREB in the brain. Moreover, this work supports previous studies suggesting that the effect of GLP-1 analogues in models of brain damage relates to GLP-1 receptor stimulation in a dose-dependent manner. Keywords: GLP-1, Traumatic Brain Injury, TBI, sitagliptin, liraglutide, CREB, Oxidative Stress, GIP, DPP-IV, DPP-4